The story of Jumping Mouse : a native American legend - Steptoe, John, 1950-1989 (Lothrop, Lee & Shepard Books, 1984)
The gifts of Magic Frog and his own hopeful and unselfish spirit bring Jumping Mouse finally to the Far-Off Land where no mouse goes hungry.